Gone with the forest: Assessing global woodpecker conservation from land use patterns. Issue 5 (21st January 2018) - Vergara‐Tabares, David L.; Lammertink, Martjan; Verga, Ernesto G.; Schaaf, Alejandro A.; Nori, Javier
Abstract: Aim: As a result of their ecological traits, woodpeckers (Picidae, Aves) are highly sensitive to forest cover change. We explored the current land cover in areas of high species richness of woodpeckers to determinate regions where urgent conservation actions are needed. In addition, we identified woodpecker species that are sensitive to forest loss and that have high levels of human habitat modification and low levels of protection (through protected areas) in their distribution ranges. Location: Global. Methods: We joined available range maps for all extant 254 woodpecker species with information of their conservation status and tolerances to human habitat modifications and generated a richness map of woodpecker species worldwide. Then, we associated this information (the richness pattern and individual species' maps) with land cover and protected areas (PAs) maps. Result: We found that the foremost woodpecker species richness hotspot is in Southeast Asia and is highly modified. At the second species richness hotspot in the eastern Andes, we observed a front of deforestation at its southern extreme and a greater deforested area in its northern extreme but most of its area remains with forest coverage. At the species level, 17 species that are sensitive to forest modification experience extensive deforestation and have low extents of PAs in their ranges. Main conclusions: The most diverse woodpecker hotspots are mostly occupied by human‐modified landscapes, and a large portion of the species there avoids anthropogenic environments. The level of representation of woodpecker species in PAs is low as a global general pattern, although slightly better in Asia. Our global analysis of threats to woodpecker from land use patterns reiterates the urgent conservation needs for Southeast Asian forests. Finally, based on our results, we recommend a re‐evaluation for inclusion in the Red List of five woodpecker species.